Fostering Eudaimonia, Joy, and Connection among Resident Physicians: A Pilot Study: - Iyinbor, Angelina; Doolittle, Benjamin (International Journal of Innovative Research in Medical Science, 2023)
Objective: To design an effective and accessible intervention to foster joy in medicine and connection among resident physicians. Background: Physician thriving is a complex construct captured by Aristotle’s concept of eudaimonia: doing good and feeling good about one’s work. Prior studies among resident physicians proposed social connection and joy in medicine as important factors for resident thriving. We hypothesize that our intervention of combining the Three Good Things (3GT), a positive psychology exercise, and a weekly family-style dinner reflecting upon the 3GT would help develop these domains and cultivate eudaimonia. Methods: A pilot study of the two interventions was conducted between February 13 to February 27, 2023 among internal medicine and medicine-pediatrics residents (PGY1-PGY4) at a single institution. Participants completed the 3GT exercise daily. Several validated instruments were completed at project enrollment, mid-way through the intervention, and one month after completion: the Two-Question Maslach Burnout Inventory, the Professional Quality of Life Scale, which assesses for burnout, compassion fatigue, and compassion satisfaction, and the Harvard Flourishing Index. This protocol was approved by the Institutional Review Board of the Yale University School of Medicine. Results: Seven residents enrolled and five completed the project, of which three completed all three of the surveys (pre-, midpoint, and post-project). Burnout decreased in 1 (33%) of participants at the midpoint of the study and in 3 (100%) after one month. Compassion satisfaction improved in 2 (67%) of participants both midway through the study and at one month follow up. Flourishing increased in 1 (33%) of participants midway and 2 (67%) at one month post study completion. All participants acknowledged increased awareness of positive experiences after beginning 3GT exercises. All participants expressed desire in expanding family dinners to the entire program and found them helpful in building community. Conclusion: The 3GT and family style dinners are helpful interventions in fostering compassion satisfaction, connection, and positive reflections, and decreasing burnout. Further study with a larger sample size, in other programs, is necessary to provide generalizability. Including regular family style dinners at a program-wide level may increase thriving.